Sound Velocity Profile (SYP) at Strait of Malacca for Maritime Warfare Usage - Yolhamid, Mohd Najib Abdul Ghani; Abdul Rahman, Ainul Husna; Mohd Naiem, Mohd Azzeri; Razali, Mohd Norsyarizad; Ahmad, Mohd Arif (International Journal of Integrated Engineering, 2020)
Nowadays, many tragedies and accidents happen in the oceans due to human negligence in handling equipment and also the ship itself. Therefore, it is important to do the hydrographic survey as it is the study about the physical of the sea. In the other words, the hydrographic survey also comes out with the prediction of their change over time, for the primary purpose of safety of navigation and in support of all other marine activities, including the economic development, security and defences, scientific research, and environmental protection. The sound velocity profile is a plot of propagation speed or velocity of sound as a function of depth and it is a fundamental tool for predicting how the sound will travel. The sound velocity profiles around the world are different. There are three factors affecting the sound velocity profile which is temperature, salinity, and pressure. The survey to get the sound velocity profile is using the sound velocity probe. The survey was done at 9 chosen locations at Straits of Malacca to get their sound velocity profile. The data from the sound velocity probe from the survey being collected by the hydrographic department and the sound velocity profile for 9 chosen locations at Straits of Malacca have been plotted. Therefore, the profile can be used as a reference for the tactical warfare usage and also for calibration of the echo sounder on board the ship.